2017
DOI: 10.15244/pjoes/65039
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Effects of Aqueous Extracts of Alternanthera philoxeroides on the Growth of Zoysia matrella

Abstract: Alternanthera philoxeroides is a perennial invasive species worldwide which can greatly affect native ecosystems and agricultural production. Our research studied the allelopathic effects of aqueous extracts of A. philoxeroides on the growth and antioxidant enzyme activities of Zoysia matrella, and isolated and analyzed the dominant allelochemicals in root extracts of A. philoxeroides. The overall allelopathic effects of A. philoxeroides extracts on the growth and antioxidant enzyme activities of Z. matrella w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Additionally, we also discovered that low concentrations of both A. corniculatum LLLs and PCTs promoted the germination and growth of K. obovata, e.g., initiation time of stems, number of roots, and length of roots. This interesting trend was consistent with a previous discovery that low concentrations (less than 10 g L −1 ) of Alternanthera philoxeroides extract could facilitate the growth of Zoysia matrella [36]. We speculated that these observations might be because a small number of CTs acted as "antigens" to activate the defense mechanisms and then triggered the production of various enzymes to adapt to adverse situations.…”
Section: Allelopathic Response Indices Of a Corniculatum's Physiological Performance Under Lll And Pct Treatments From K Obovatasupporting
confidence: 91%
“…Additionally, we also discovered that low concentrations of both A. corniculatum LLLs and PCTs promoted the germination and growth of K. obovata, e.g., initiation time of stems, number of roots, and length of roots. This interesting trend was consistent with a previous discovery that low concentrations (less than 10 g L −1 ) of Alternanthera philoxeroides extract could facilitate the growth of Zoysia matrella [36]. We speculated that these observations might be because a small number of CTs acted as "antigens" to activate the defense mechanisms and then triggered the production of various enzymes to adapt to adverse situations.…”
Section: Allelopathic Response Indices Of a Corniculatum's Physiological Performance Under Lll And Pct Treatments From K Obovatasupporting
confidence: 91%
“…Additionally, we also discovered that low concentrations of both A. corniculatum LLLs and PCTs promoted the germination and growth of K. obovata, e.g., initiation time of stems, number of roots, and length of roots (Figures 2-3, Table 1). This interesting trend was consistent with a previous discovery that low concentrations (less than 10 g L -1 ) of Alternanthera philoxeroides extracts could facilitate the growth of Zoysia matrella [37]. We speculated that these observations might be because a small amount of CTs acted as "antigens" to activate the defense mechanisms, and then triggerred the production of various enzymes to adapt adverse situation.…”
Section: Condensed Tannins Extracted From Leaf Litter Primarily Contribute To Allelopathy In Mangrove Forestssupporting
confidence: 91%
“…Different extracts of Cassia tora organs inhibited seed germination and seedling growth of mustard (Sarkar et al,) of mustard (Sarkar et al, 2012). The strength of the allelopathic effects of roots', leaves' and stems' extracts of A. philoxeroides on Z. matrella diminished subsequently (Huang et al, 2017) but no information was found about the allelopathic effects of L. spectabilis and A. cordifolia. The number of chromosomes in meiosis revealed that the number of chromosomes of A. cordifolia is n=6 (2n=12) and n=9 (2n=18) for L. spectabilis (syn: mesembryanthemum spetabila).…”
Section: Discussionmentioning
confidence: 99%
“…Allelopathy effects of L. spectabilis and A. cordifolia were associated with small inhibitory effects on seed germination and seedlings growth of mungbaen. Allelopathic effects of both plant extracts, in particular A. cordifolia, were significant on barley seed germination and growth of seedlings.The extracts of Triantheum portulacastrum (Aizoaceae) reduced seed germination and seedling growth of Sesamum indicum (Huang et al, 2017). Different extracts of Cassia tora organs inhibited seed germination and seedling growth of mustard (Sarkar et al,) of mustard (Sarkar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%